Penerapan Konsep Ecogreen (Budidaya Lele dan Sayur Organik) Pada Lahan Terbatas dan Padat Penduduk di Dasawisma Hidayatullah Kelurahan Karang Asam Ulu - Roby; Abidin, Zainal (Jurnal Kabar Masyarakat, 2023)
The problem of narrow land is a problem that is often experienced by people in densely populated settlements, including Karang Asam Ulu Village which is a community service partner. Limited land makes it difficult to develop crop and fish cultivation, so it cannot meet family food needs. Cultivation in buckets (Budikdamber) is the right solution to overcome limited land because it does not require large areas for vegetable and fish cultivation. The purpose of this service is to provide community knowledge and skills to the Dasawisma group of Karang Asam Ulu Urban Village RT 024, Sungai Kunjang Subdistrict, Samarinda City in utilizing yard land to be used as Budikdamber. The stages of implementation began with a field survey and then continued with a focus group discussion (FGD) to explore information and problem-solving. The results of the FGD were followed by socialization and practice in making Budikdamber. Every activity is monitored and evaluated to assess the success of the program. From the training results, it was found that the Dasawisma of Karang Asam Ulu Village already knew how to make a Budikdamber.